Knowledge, attitudes and practices of primary care professionals about the food guide for children up to 2 years old: a cross-sectional study, Botucatu, São Paulo, Brazil, 2023 - Amaral, Vivian Lovison Do [UNESP]; Spadotto, Giovana Canela [UNESP]; Gomes, Caroline de Barros [UNESP] (FapUNIFESP (SciELO), 2024)
Objective: To investigate knowledge, attitudes and practices of primary health care professionals regarding breastfeeding and complementary feeding, in accordance with the recommendations of the food guide for Brazilian children up to 2 years old. Methods: This is a descriptive study undertaken from October to December 2023, with a self-administered online questionnaire, aimed at physicians, nurses and community health agents in primary health care in Botucatu, São Paulo, Brazil. We performed descriptive analysis and used Pearson’s chi-squared test to analyze association between professional categories and their knowledge, attitudes and practices in relation to the content of the food guide. Results: 74 professionals participated, including 37 community health agents, 19 nurses and 18 physician. Half the professionals had low knowledge about the content of the guide, getting less than half the answers right, in particular those related to complementary foods, for which 57 professionals got less than half of them right. Physicians and nurses were the professionals who believed they were more qualified to provide information related to the content of the guide, when compared to community health agents (p-value<0.001). Regarding practices, 18 professionals stated they sometimes provide guidance on breastfeeding, 24 reported never doing breastfeeding assessments during consultations and home visits and 22 provided guidance on introduction of complementary feeding. Conclusion: Knowledge of physician, nurses and community health workers was deficient regarding the content of the guide. Attitudes and practices regarding the content were also compromised.
Conocimientos, actitudes y prácticas de profesionales de atención primaria sobre la guía alimentaria para niños de hasta 2 años: estudio transversal, Botucatu, São Paulo, Brasil, 2023
Conhecimento, atitudese práticas de profissionais da atenção primári as obreoguia alimentar para criançasaté 2 anos: estudotr ansversal, Botucatu, São Paulo, 2023
Keywords: Breastfeeding; Cross-Sectional Studies; Food Guides; Infant Nutrition; Primary Health Care